Unseen WEIRD Assumptions: The So-Called Language Gap Discourse and Ideologies of Language, Childhood, and Learning. Issue 1 (2nd January 2017) - Blum, Susan D.
ABSTRACT: Claiming to rely on "science, " many well-intentioned "experts" offer advice on how to "close the gap"—word gap, language gap, achievement gap—between disadvantaged and advantaged children. Based on both research and personal experience, this advice promises magic solutions to apparently complex and intractable problems by coaching disadvantaged parents in how best to speak to their young children. One significant shortcoming, however, is that the research is often circular, mistaking correlation and causation, and it is based on limited populations—what Henrich et al. (2010) termed WEIRD populations of Western, Educated, Industrialized, Rich, and Democratic people, often majority undergraduate college students in North America. The unseen assumptions about what is "natural" or "optimal" may be evident when cross-cultural evidence is brought to contrast with the assumed proper way to socialize children into language—ways familiar to White, middle-class, professional North American practitioners. This article reveals three of the dominant ideologies governing the "gaps" discourse: parochial understandings of language, childhood, and learning. Ultimately, I argue that accepting diverse aspects of all these concepts can give rise to flourishing human beings.